1999
DOI: 10.1002/etc.5620180228
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and reproductive toxicity of a mixture of 15 methylsulfonyl‐polychlorinated biphenyls and 3‐methylsulfonyl‐2,2‐bis‐(4‐chlorophenyl)‐1,1‐dichloroethene in mink (Mustela vison)

Abstract: Abstract-A synthetic mixture of 16 aryl methyl sulfones was given in the feed to female mink for one year (three times a week, resulting in a mean daily exposure of 0.1 mg/mink). The mink were mated after 9 months of exposure and the reproductive outcome was studied. The dams and kits were examined for biochemical and toxic effects. The litter size was significantly increased (50%) in the exposed group, and the mean birth weight was 20% lower than that of the controls. Kit survival was 47% by 2 weeks after bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Finally, MeSO 2 -PCBs are also capable of reducing thyroid hormone levels in laboratory animals (Kato et al, 1998, Kato et al, 1999, Kato et al, 2000). These effects, were observed both in mink dams and also in their offspring, where metabolites were transferred from mothers (Lund et al, 1999). …”
Section: Pcb Metabolite Associated Toxicitiesmentioning
confidence: 99%
“…Finally, MeSO 2 -PCBs are also capable of reducing thyroid hormone levels in laboratory animals (Kato et al, 1998, Kato et al, 1999, Kato et al, 2000). These effects, were observed both in mink dams and also in their offspring, where metabolites were transferred from mothers (Lund et al, 1999). …”
Section: Pcb Metabolite Associated Toxicitiesmentioning
confidence: 99%
“…A PCB and DDE methylsulfone mixture may actually increase the litter size in mink (Mustela vison). 27 The marked localization of MeSO 2 -PCBs to the lungs has been discussed in relation to the respiratory distress observed among PCB-intoxicated Yusho patients in Japan. 28 Monohydroxy as well as dihydroxy metabolites of PCBs have been found in numerous species, including rats, guinea pigs, and seals.…”
Section: Pcb Metabolitesmentioning
confidence: 99%
“…Kato et al (1997) reported that only meta-substituted MeSO 2 -CBs strongly induced CYP2B1/2 and reduced the serum thyroid hormone level in rats. Exposure of minks to a synthetic mixture of meta-and para-MeSO 2 -CBs also resulted in the selective retention of meta-MeSO 2 -CBs in the liver and increased induction of some hepatic CYP2B isozymes as well as alteration of thyroid hormone levels in blood (Lund et al, 1999). Higher levels of induction of CYP2B1/2 by MeSO 2 -CBs as well as induction of CYP3A-like activity (Schuetz et al, 1986(Schuetz et al, , 1998 may alter the metabolic pathways of individual PCBs in rats and contribute to the high level of toxicity of nonplanar PCBs.…”
Section: Discussionmentioning
confidence: 99%